HISTORICAL FACTORS OF THE CULTURAL ENVIRONMENT IN THE EDUCATIONAL SPACE (Scientific journal of the Fergana State University, 2023)
In this article, it is stated that for the emergence of a person who can purposefully engage in educational activities in a society, there must be a certain environment as well as appropriate social conditions-a society in which the reputation of the teacher is high. the ability to select the most talented people for the field of education, the cultural environment in education, the necessary conditions for the creation of an educational space in a stable society, as well as historical, political, economic, social, and cultural factors, pedagogues working in the field of education create a cultural environment that is stated to be necessary to know.